(untitled) (Research, Society and Development, 2022)
Burns follow men since the beginning and, due to population growth, accidents of this type are becoming more common. According to the WHO, burns are the fourth most common trauma, with 7.1 million people affected per year, of which 180,000 die. There are several solutions used over the years for burns, among them, tilapia skin. Therefore, this study aims to collect data and evidence about the use of tilapia skin, evaluating healing time, costs, adverse reactions and treatment efficacy. Articles were collected in the MEDLINE, LILACS and Cochrane databases, with the descriptors “Burns”, “Oreochromis niloticus” and “treatment”, during the month of August 2021. Subsequently, a careful analysis of the selected material was carried out in order to gather the most relevant information concerning the proposed topic. Nine articles out of the 25 found with the search were included in the review, the objectives and main results found in the articles were summarized in a table. It can be concluded from this review that there are numerous advantages of using tilapia skin and how it has great potential to reduce the patient’s suffering during treatment.